2011
DOI: 10.1002/ijc.25807
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen‐G expression is associated with a poor prognosis in patients with esophageal squamous cell carcinoma

Abstract: Human leukocyte antigen (HLA)‐G inhibits functions of immune component cells and promotes malignant cells evading from antitumor immunity. We investigated the clinical relevance of HLA‐G expression in esophageal squamous cell carcinoma (ESCC). In our study, HLA‐G expression in 79 primary ESCC lesions and corresponding adjacent normal tissues were analyzed with immunohistochemistry. Soluble HLA‐G (sHLA‐G) in plasma was detected with enzyme‐linked immunosorbent assay (ELISA) in 41 ESCC patients (including 19 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 48 publications
4
35
0
Order By: Relevance
“…In hepatocellular carcinoma, HLA-G expression was found to be strongly correlated to advanced disease stage, and more frequently observed in elder patients [17]. Similar correlation was also observed in non-small cell lung cancer [18,19], gastric carcinomas [20], colorectal cancer [21] and esophageal squamous cell carcinoma patients [22,23] that lesion HLA-G expression was strongly correlated to disease stage and poor prognosis and that HLA-G was an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 68%
“…In hepatocellular carcinoma, HLA-G expression was found to be strongly correlated to advanced disease stage, and more frequently observed in elder patients [17]. Similar correlation was also observed in non-small cell lung cancer [18,19], gastric carcinomas [20], colorectal cancer [21] and esophageal squamous cell carcinoma patients [22,23] that lesion HLA-G expression was strongly correlated to disease stage and poor prognosis and that HLA-G was an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 68%
“…Previously, it was demonstrated that aberrant expression of HLA-G was associated with poor clinical outcomes in various types of carcinoma [16,[22][23][24][25][26][27][28][29][30] including breast cancer [14,31]. Therefore, our current findings suggests that HLA-G is may be an unfavorable prognostic predictor among breast cancer molecular subtypes since patients with non-luminal subtypes have a poorer prognosis than the luminal subtypes [2,3].…”
Section: Discussionmentioning
confidence: 61%
“…However, more studies on the complete HLA-G gene and its linkage disequilibrium with other genes and on HLA-G expression at both the tumor site and plasma in a specific microenvironment are required to consolidate these findings. carcinoma (69,70), esophageal squamous cell carcinoma (71)(72)(73)(74), gastric cancer (75)(76)(77), glioblastoma (78), hepatocellular carcinoma (79)(80)(81), lung cancer (82)(83)(84), nasopharyngeal carcinoma (85), oral cavity squamous cell carcinoma (86), ovarian cancer (87-89), pancreatic adenocarcinoma (90), thyroid carcinoma (91,92). These data were summarized in Table 1.…”
Section: Relevance Of Hla-g Expression In Cancersmentioning
confidence: 99%